Investigação teórica de processos catalíticos homogêneos promovidos por compostos organometálicos - Roberta Pereira Dias (2012)
In this work were performed electronic structure calculations, which were conducted in order to understand the mechanism of the hydroformylation reaction, as well as to investigate the factors responsible for the control of selectivity. We performed three different studies, covering the key issues of the origin of the selectivity in the reaction and the nature of the catalyst, substrate and the stereo-electronic properties of the ligands. In the first study, the origin of regioselectivity in rhodium disphosphine catalyzed hydroformylation was investigated by means of hybrid QM/MM calculations. We succeeded in reproducing some trends observed experimentally as, for instance, the high selectivity of the HRh(BISBI)(CO) for the linear aldehyde. The results also showed that the regioselectivity is mainly governed by interactions between the diphosphine substituents and the substrate, while the effects directly associated to the bite angle have a smaller influence. We also have applied DFT calculations to investigate the electronic and special effects of phosphorus ligands on the selectivity of the olefin (propene and styrene) insertion reaction into the Rh-H bond of rhodium-based complexes. The calculations revealed that the olefin coordination and insertion reactions are dominated mainly by the electronic effects of the phosphorous ligands. Using propene as the substrate and for all the phosphorus ligands investigated, the insertion always proceeds through the reaction path leading to the linear metal-alkylintermediate. However, when styrene is used, the branched metal-alkyl intermediate is always favored. In order to analyze the stereo-electronic factors of the real ligands, we performed full quantum mechanical calculations at the DFT level and ONIOM (QM/MM) level were carried out to study the full catalytic cycle for the hydroformylation of propene, catalyzed by the heterobimetallic catalyst transHPt(PPh3)2(SnCl3) with real triphenylphosphine ligands. The quantum mechanical calculations showed that regioselectivity of the hydroformylation are set at the olefin insertion step, with the aldehyde reductive elimination being the rate-determining step of the entire cycle, with an activation free energy of 18.1 kcal/mol, in line with the experimental findings.